The Homelanders: The Last Thing I Remember - Book 1 - Klavan, Andrew (Nashville, Tenn. : Thomas Nelson, 2009)
Charlie West wakes up to the discovery that he has amnesia and remembers nothing about escaping from prison or why he is being pursued by both the law and a group of terrorists trying to bring down the government of the United States.
Includes reading group guide.
Keywords: Amnesia -- Fiction; Terrorism -- Fiction; Adventure fiction